If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7p-7)=10(2p+6)-7(-2+2p)
We simplify the equation to the form, which is simple to understand
(7p-7)=10(2p+6)-7(-2+2p)
Remove unnecessary parentheses
7p-7=10*(2p+6)-7*(-2+2p)
Reorder the terms in parentheses
7p-7=+(+20p+60)-7*(-2+2p)
Remove unnecessary parentheses
+7p-7=+20p+60-7+*(-2+2p+)
Reorder the terms in parentheses
7p-7=+20p+60+(+14-14p)
Remove unnecessary parentheses
+7p-7=+20p+60+14-14p
We move all terms containing p to the left and all other terms to the right.
+7p-20p+14p=+60+14+7
We simplify left and right side of the equation.
+1p=+81
We divide both sides of the equation by 1 to get p.
p=81
| 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 | | 13x+(x+3)+(x+2)+(x+7)=40 | | 6x^3-5x^2+1=0 | | -3x-14+10x=-2 | | -6(v+7)=9v+48 | | 2(3x+8)+6(x-1)=-12 |